AGING AND THE PSYCHONEUROENDOCRINE SYSTEM - Alvarez, X. Antón; Franco, Andrés; Cacabelos, Ramón (Anales de Psicología / Annals of Psychology)
The effects of aging on different neuroendocrine systems are reviewed. Aging provokes dramatic changes in most of the hierarchically-organized neuroendocrine axes. Some of these changes are associated with behavioural and mental changes appearing in normal and pathological aging. A better knowledge of the neuroendocrine aging processes will allow to employ neurobiological and molecular genetics techniques and drugs in order to treat psychogeriatric diseases.